A survey of availability, price and affordability of essential medicines from 2011 to 2016 in Chinese secondary and tertiary hospitals - Xiaodong Guan; Huajie Hu; Chunxia Man; Luwen Shi (BMC, 2018)
Abstract Background Essential medicines are those drugs that satisfy the priority health care needs of the population and help with functioning healthcare systems. Although many countries have formulated an essential medicine list, almost half of the global population still lack regular access to essential medicines. Research about the initiation of National Essential Medicines Policy in Chinese secondary and tertiary hospitals is inadequate, and the long-term effect on access after the reform is still unknown. This study's objective was to investigate the access to essential medicines in mainland China's secondary and tertiary hospitals. Methods Data on the access to 30 essential medicines from China's National Essential Medicine List were obtained from China Medicine Economic Information database covering 396 secondary hospitals and 763 tertiary hospitals. We improved the standard methodology developed by the World Health Organization and the Health Action International to measure the availability, median price ratio (MPR) and the incidence of catastrophic drug expenditure (CDE). Results Five essential medicines had > 50% availability and the nationwide availability kept steady; availability of drugs in eastern regions of China was significantly higher than the central and western regions. The median MPR of 30 drugs nationwide kept steady approximately 5; MPR of drugs in the eastern regions was significantly higher than the central and western regions and the ratio of MPR of innovator brands to generics increased from 3.66 to 6.32 during the study period. The incidence of CDE caused by essential medicines decreased from 2011 to 2014; brand name medicines were more likely to cause CDE than generics and rural patients have a greater tendency to fall into CDE. Conclusions After the implementation of National Essential Medicines Policy, the MPR of essential medicines was well controlled and became more affordable in the context of steady availability. This has highlighted the problems associated with region disparity and inequity between rural and urban areas in the delivery of essential medicines and sustainable mechanisms are needed to deepen the National Essential Medicines Policy in mainland China.